1989
DOI: 10.1016/0014-5793(89)81790-9
|View full text |Cite
|
Sign up to set email alerts
|

In vivo activity of the most proximal promoter of the human aldolase A ene and analysis of transcriptional control elements

Abstract: The genomic region upstream from exon F (exon IV) of the human aldolase A gene has been studied for its ability to direct the transcription of a reporter gene in vivo. Transfection experiments in human hepatoma cells (Hep 3B) followed by CAT assay, and S, mapping analysis, demonstrated that: (i) this region is able to drive CAT gene transcription; (ii) all the transcriptional control elements of this promoter are downstream from nucleotide -384 of the longer ubiquitous RNA start site and the sequences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The availability of soluble ZNF224 molecules and accessibility of its cognate motif on the AldA-NRE in the distal promoter of the aldolase A gene are prerequisites for full ZNF224-mediated transcription repression. Coordinated regulation of aldolase A gene transcription involves multiple cis-elements located in the promoter regions upstream from leader exons L1, M, and F that interact with several nuclear proteins (Izzo et al, 1989;Concordet et al, 1991;Costanzo et al, 1993;Salminen et al, 1994;Lupo et al, 1995Lupo et al, , 1997. A negative regulatory element could determine the timing and distribution of transcription during development.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The availability of soluble ZNF224 molecules and accessibility of its cognate motif on the AldA-NRE in the distal promoter of the aldolase A gene are prerequisites for full ZNF224-mediated transcription repression. Coordinated regulation of aldolase A gene transcription involves multiple cis-elements located in the promoter regions upstream from leader exons L1, M, and F that interact with several nuclear proteins (Izzo et al, 1989;Concordet et al, 1991;Costanzo et al, 1993;Salminen et al, 1994;Lupo et al, 1995Lupo et al, , 1997. A negative regulatory element could determine the timing and distribution of transcription during development.…”
Section: Discussionmentioning
confidence: 98%
“…Regulation of the aldolase A gene involves multiple ciselements located within the promoter regions upstream from leader exons L1, M and F that interact with several nuclear proteins (Izzo et al, 1989;Costanzo et al, 1993;Concordet et al, 1991;Lupo et al, 1995). The differential expression of various aldolase A mRNAs (L, M and F types) is controlled by interaction between DNA and proteins according to cell and stage specificity (Salminen et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription of multiple mRNA species (L, M, and F types), containing the same coding region but different untranslated 5Ј-ends, is driven by three autonomous promoters and splicing of alternative leader exons (L, M, and F) (1-3). In man, two of these mRNA species (L and F types) are ubiquitously expressed, whereas the third one (M type) is muscle-specific (4 -6).We have demonstrated that the human genomic regions upstream from exons F and L are able to drive autonomous transcription (7,8). We found that the basal transcriptional activity of pF is regulated by several binding sites for the ubiquitous factor Sp1 (7).…”
mentioning
confidence: 81%
“…Regulation of the aldolase A gene involves multiple cis-elements located within the promoter regions upstream from leader exons L1, M, and F that interact with several nuclear proteins (7)(8)(9)(10)(11). The differential expression of various aldolase A mRNAs (L, M, and F types) is controlled by an interplay of interactions between DNA and proteins according to cell and stage specificity (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation